Effect of potassium application on growth, yield and economics of sunflower (Helianthus annuus L.) - Fida Mohammad Zaki; V.K. Singh; S.S. Rathore; B.A. Sarvari; Mohammad Ali Manandoi (Annals of Agricultural Research, 2023)
A field experiment was conducted at research farm of National Agricultural Science and Technology University (ANASTU), Kandahar, Afghanistan during summer season 2016-17. The treatments consisted of two factors, potassium levels (four) 0 kg K2 O/ha, 30 kg K2 O/ha, 60 kg K2 O/ha and 90 kg K2 O/ha and varieties (three) Aftab-e-siya, Aftab-e-surkh, Canadian. All the varieties responded variably to different levels of potassium application in term sof growth, productivity. Based on the results, it is concluded that maximum plant height (136.6 cm) was recorded at 90 kg K2 O/ha. Dry matter accumulation was significantly (P